2023
DOI: 10.3390/cancers15072059
|View full text |Cite
|
Sign up to set email alerts
|

Patient Derived Organoids (PDOs), Extracellular Matrix (ECM), Tumor Microenvironment (TME) and Drug Screening: State of the Art and Clinical Implications of Ovarian Cancer Organoids in the Era of Precision Medicine

Abstract: Ovarian cancer (OC) has the highest mortality rate of all gynecological malignancies due to the high prevalence of advanced stages of diagnosis and the high rate of recurrence. Furthermore, the heterogeneity of OC tumors contributes to the rapid development of resistance to conventional chemotherapy. In recent years, in order to overcome these problems, targeted therapies have been introduced in various types of tumors, including gynecological cancer. However, the lack of predictive biomarkers showing differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…In addition, our result shows inconclusive comparative performance of PDO and PDX, which is consistent with current reports in the literature. PDOs offer advantages such as being an in vitro system with lower costs yet maintaining cellular heterogeneity [ 65 , 66 ]. However, they lack of immune system components and loss of stromal components over time represent limitations in representing the tumor microenvironment [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our result shows inconclusive comparative performance of PDO and PDX, which is consistent with current reports in the literature. PDOs offer advantages such as being an in vitro system with lower costs yet maintaining cellular heterogeneity [ 65 , 66 ]. However, they lack of immune system components and loss of stromal components over time represent limitations in representing the tumor microenvironment [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study suggests that the role of SMAD4 as a tumor suppressor is more complex than currently appreciated and may have implications in the understanding of cancer invasion. Already, new PDO studies have suggested that new therapies and targets for late-stage cancer treatments must consider the surrounding environment [79,84,87,88]. Thus, it would be exciting to further delve into the conditions for SMAD4-dependent gene regulation in different tumor microenvironments, and the continued use of organoid modeling provides a powerful foundational tool in these future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Seminal work on the generation and characterisation of PDOs in ovarian cancer has already explored their use in the screening of response to the gold standard platinum-based therapy [23] or their sensitivity to PARP inhibitors based on their DNA repair profiling [24]. By contrast, integration of the tumour microenvironment in the PDO models remains a challenge and represents a current object of study in terms of improving drug screening, particularly when used in targeted therapy and immunotherapy to guide therapeutic decisions [25]. Of particular interest, PDOs derived from malignant ascites and pleural effusions, recapitulating tumour histological features, have also been used for empirical drug testing of novel therapeutics and for RNA sequencing analysis [26].…”
Section: Discussionmentioning
confidence: 99%